The Influence of Service Quality, Facilities and Location on the Decision to Purchase Citraraya Tangerang Housing - Samudro, Amzad; Hamdan, Hamdan (Dinasti International Journal of Management Science, 2024)
This research aims to analyze the influence of service quality, facilities and location on purchasing decisions for CitraRaya Tangerang housing. Through a quantitative approach that is causal in nature, it is carried out to obtain a research model according to the procedure. This requires a sample that has been observed and determined based on the criteria of respondent characteristics using purposive sampling and 190 samples were found to ensure the sample was appropriate. This reason makes this research use the PLS analysis method approach which is the right step for analyzing research data. The results of this research are that service quality, facilities and location have a positive and significant effect on the decision to purchase CitraRaya housing. Finally, the findings of this research provide knowledge that can be relied upon in the future, especially for property business actors as an important reference in making effective marketing management strategic decisions in achieving competitive advantage.